Solid-state Air Conditioning System for Electric Vehicle Application - QING, LIM JIA (IRC, 2017)
A regular internal combustion engine (ICE) vehicle’s air conditioning system consists a compressor which is driven by the mechanical power of the internal combustion engine. Unlike the regular ICE vehicle, an electric vehicle uses electric motor and battery to propel itself. Hence, unless an electrical motor is used, it cannot utilize the conventional air conditioning system which requires mechanical power to run the compressor and pump. Therefore, a solid-state air conditioning system is proposed to be used as the energy converter to provide cooling effect to the interior air of the electric vehicle. Solid-state air conditioning system is also known as thermoelectric cooling (TEC). It is an air conditioning system which does not contain any moving mechanical parts such as compressor. It uses electrical energy and converts it into thermal energy or vice versa. Peltier device is normally used in thermoelectric cooling. It could be used to cool the internal cabin of an electric vehicle. With consumption of electrical energy, it can transfer heat from one side to another based on the path of the current. Heat sinks are usually attached to both side of the Peltier device, hence the heat energy from the can be dissipated and the hot side is maintained at room temperature, whereas the cool side can achieve a lower temperature than room temperature.